Development of Physics Digital Props Based on the Internet of Things (IoT) on the Material of Motion Dynamics (Jurnal Pendidikan Fisika, 2024)
This research aims to create an Internet of Things (IoT)-based Newton's Law II physics practicum trainer. The developed props aim to make the students understand measure time, speed, and acceleration in Particle Dynamics Using IoT-based teaching aids. The design of teaching aids uses electronic components such as ESP32 WIFI-Bluetooth microcontrollers, obstacle Infrared Sensors, and LCDs as the main hardware components. The software for developing this teaching aid utilizes the Arduino IDE compiler based on C++. The development research method used is the ADDIE design development method. The ADDIE design development stages include Analyze, Development, Implementation, and Evaluation. The product feasibility test involved 35 SMAN 1 Montong Gading students. Expert validators in the media and material carry out the feasibility test. The feasibility test results in the media and material sector are 95%, with a very feasible category. The scores of the student's responses to the development are 77% with a practical. The results showed that the physics teaching aids developed were very valid and feasible to use.
Keywords: development; internet of things (iot); learning physics; props